SOCIAL ENTERPRISES LEADING AS THE WAY IN THE CIRCULAR ECONOMY IN UKRAINE - К.Ю. Редько (Ekonomìčnij Vìsnik Nacìonalʹnogo Tehnìčnogo Unìversitetu Ukraïni "Kiïvsʹkij Polìtehnìčnij Institut")
In the article shows that due to the introduction of martial law and hostilities in a significant territory of Ukraine, there is a rapid increase in unemployment, an increase in the number of vulnerable categories of the population, and a weakening of their social protection. It is shown that under these conditions, social entrepreneurship can smooth out several pressing issues in society, as well as speed up their resolution. The activities of social enterprises contribute to solving the problems of socially vulnerable people, their employment, and social adaptation. In the article, the author defined social entrepreneurship as an innovative entrepreneurial activity to obtain profit, which is aimed at solving/mitigating social problems and achieving positive changes in society. The author shows that social enterprises play one of the most relevant roles in the process of transitions from a linear to a circular economy. Such companies use innovative strategic thinking to reduce environmental impact and create higher added value to society because the core business mission is a social one; special attention to sustainability is given by the stakeholders who must be involved in the transition process, such as policymakers, technology, and innovation centers, researchers. In the article, the author investigated the achievement of the mission of social enterprises is in various ways: the sale of goods of own production, the support of various projects (social, cultural, sports), and the employment of representatives of vulnerable groups of the population. In this case, one enterprise can engage in different activities at the same time. Social entrepreneurship is a business solution to acute social problems. This concept differs from charity and traditional business in its way of independence from financial donors and external one’s sources of funding and the opportunity to have status non-profitability, as it is not created for the sake of benefits or power preferences.